2019
DOI: 10.15252/embj.201899599
|View full text |Cite
|
Sign up to set email alerts
|

EZH 2 cooperates with gain‐of‐function p53 mutants to promote cancer growth and metastasis

Abstract: In light of the increasing number of identified cancer‐driven gain‐of‐function (GOF) mutants of p53, it is important to define a common mechanism to systematically target several mutants, rather than developing strategies tailored to inhibit each mutant individually. Here, using RNA immunoprecipitation‐sequencing (RIP‐seq), we identified the Polycomb‐group histone methyltransferase EZH2 as a p53 mRNA‐binding protein. EZH2 bound to an internal ribosome entry site (IRES) in the 5′UTR of p53 mRNA and enhanced p53… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 80 publications
(133 reference statements)
1
34
1
Order By: Relevance
“…5 × 10 6 C4-2 cells treated with 100 µM 4-Thiouridine (4SU) for 8 h were washed with cold PBS one time and cells were irradiated once with 150 mJ/cm 2 at 365 nm using a Startalinker 38 . Cells were lysed in lysis buffer (50 mM Tris-HCL, pH 7.4, 100 mM NaCl, 1% NP-40, 0.1% SDS, 0.5% sodium deoxycholate, protease inhibitor cooktail and RNase inhibitors) with protease inhibitors (1 mL) and transferred to 1.5 mL microtubes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 × 10 6 C4-2 cells treated with 100 µM 4-Thiouridine (4SU) for 8 h were washed with cold PBS one time and cells were irradiated once with 150 mJ/cm 2 at 365 nm using a Startalinker 38 . Cells were lysed in lysis buffer (50 mM Tris-HCL, pH 7.4, 100 mM NaCl, 1% NP-40, 0.1% SDS, 0.5% sodium deoxycholate, protease inhibitor cooktail and RNase inhibitors) with protease inhibitors (1 mL) and transferred to 1.5 mL microtubes.…”
Section: Methodsmentioning
confidence: 99%
“…Cell invasion assay in vitro was performed with Corning matrigel invasion chamber assay according to manufacturer's instructions as previously described 38 . Briefly, cells were diluted to 3 × 10 4 cells per well in serum-free medium and plated to the inside of matrigel chamber in 24-well plates, outside the chamber was added the medium with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…Provocatively, it was recently reported that EZH2 directly binds to the internal ribosome entry site (IRES) on the mRNAs of both wild-type and mutated p53, leading to enhanced translation of p53 protein, especially mutant one, and subsequently promoted cancer growth and metastasis. However, this EZH2-RNA interaction seems to be independent of EZH2's methyltransferase activity (Zhao et al, 2019). These studies present a diverse and complex picture of EZH2 functions in regulation of DDR.…”
Section: Introductionmentioning
confidence: 90%
“…EZH2 gene is a member of the Polycomb-group (PcG) family, is a core subunit of the polycomb repressor complex 2 (PRC2), participates in the formation of multimeric protein complexes to maintain the transcriptional repressive state of genes over successive cell generations 12. EZH2 has abnormal expression in almost all malignant cancers 13-16.…”
Section: Introductionmentioning
confidence: 99%